(untitled) (Bulletin KNOB, 1990)
The urban identity of Rotterdam certainly cannot be defined in terms of historical fixation. The notion identity is synonymous with the evolutionary way urban space and human activities are being exploited. As opposed to the imago of the town whereby architecture and town-planning are greatly form defining identity is a much more complex notion combining social and psychological values and geographically determined urban spaces. European Darwinism makes competing towns handle marketing techniques to attract business and population. Also Rotterdam can be characterized as a consumer town where leisure activities are as important as economical potency. Small mobile households with a large enough income to go out a lot contrast sharply with the ’city of the permanent underclass’ to which living accommodations are of primary importance. Because of this dissension the ’image building’ of the town is being forced to aim at the marked and large projects, which approach even has taken on (inter)provincial dimensions. The problem on urban identity has shifted to the entire rim-shaped agglomeration of cities in the western part of the Netherlands. During the sixties Functional Modernism made rebuilt Rotterdam derive her identity from harbour activities. The seventies were characterized by urban renewal and social housing, which problems have been solved on the level of the neighbourhood or quarter. Present attraction of businesses however leads to an area planning affecting the total urban infrastructure. Attention concentrates on sensitive spots and trajects and the coherence the approach of these bottlenecks could realize. Although these proposals discuss the ’experience’ of the entire town their concentration on economical locations comprises the danger of fragmentation. Upperlocal politics wants to confine the aesthetics of urban space to an identification with fragmented spaces. This attitude denies the conception of the town-centre as the only urban identity thus meeting economical development as well as the demands of the different sections of the population. Structural principles missing the lay-out of industrial sites in Rotterdam’s peripheral zone is being defined by esthetical elements and lines from the surrounding landscape. The competition between cities gives the notion of the individual urban identity special dynamics leading to merely imago-directed actions. Because of a supposed loss of identity the municipality of Groningen commissioned architect Daniel Libeskind to design a new image with contemporary means. From static conception pointing at the past the content of urban identity has changed into the notion of identity as working hypothesis.